ANALISIS STOCK SPLIT TERHADAP RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahyuni, Etty Sri; Faisal, Yusuf; Ramadhan, Faris; Putra, Tri Wildan Rosyadi (Universitas Batam, 2020)
The function of the capital market is a place where buyers and sellers meet in buying shares. The level of risk or uncertainty faced in the world of capital markets must be embedded in all the investments offered, so the level of investment cannot only rely on profit. A Capital market that reacts quickly and accurately is an efficient market. The purpose of this study was to examine the role of the stock split on stock returns and stock trading volume. The research objects were 25 manufacturing companies that carried out a stock split in 2016. The data analysis technique used was the paired sample t-test. The results of the study did not have a significant effect on stock split announcements on stock returns. There is a significant effect of the announcement of the stock split on the volume of stock trading